A Novel Method for Bending Stiffness Evaluation of Bus Body. (January 2015) - Na, Jingxin; Yuan, Zheng; Gao, Jianfeng
Bending stiffness is an important factor to determine the mechanical performance of bus body skeleton. Traditional computational method for bending stiffness is sensitive to local deformation and load applications, which often results in great fluctuation to the computational results. This paper proposes an advanced computational method for bending stiffness based on deformable feature curve of bus body. Firstly, the feature point collection from the deformation of bus body under bending conditions is extracted. Secondly, all the feature points are processed by means of coordinate transformation and then the feature curve of bus body deformation is established via piecewise cubic curve-fitting. Lastly, the expected value of bending stiffness of bus body is obtained through the stiffness samples which are computed according to the feature curve. Furthermore, a FORTRAN program is written to implement the method. Compared with the traditional methods, the validity and stability of this method are verified via several numerical examples. This method is meaningful to the conceptual design of a bus body, as the experimental measures are difficult to be carried out in the early stage.